2019
DOI: 10.5582/bst.2018.01234
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for patients with hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) after surgical treatment

Abstract: Hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) is rarely seen in clinical practice, and its treatment strategies and prognosis are still a subject of debate. To ascertain the characteristics of and prognosis for HCC with BDTT, 49 patients with HCC with BDTT were studied out of 763 consecutive patients with HCC who underwent surgical treatment from July 2004 to May 2018. The clinical characteristics of and prognosis for those 49 patients were reviewed and analyzed retrospectively. Of the 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Identification of this group of patients is clinically important because surgical treatment is usually beneficial 15 . Many studies have confirmed 2 , 16 , 17 that hepatic resection with removal of the BTT is the treatment of choice in selected BTT patients with resectable hepatic tumors, even for those patients presenting with obstructive jaundice.…”
Section: Discussionmentioning
confidence: 94%
“…Identification of this group of patients is clinically important because surgical treatment is usually beneficial 15 . Many studies have confirmed 2 , 16 , 17 that hepatic resection with removal of the BTT is the treatment of choice in selected BTT patients with resectable hepatic tumors, even for those patients presenting with obstructive jaundice.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding our literature review, we have extrapolated 20 articles with a total population of 890 patients [ 8 , 9 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis showed that BDTT patients with low TBIL level could benefit more from surgical resection; therefore, effective preoperative biliary drainage to reduce TBIL level to below 34 μmol/L is essential for surgery and postoperative long-term survival. During the surgery, two operative techniques mentioned in the Surgical Procedure could decrease the recurrence and metastasis rates ( 32 ), especially the peeling off technique, because it avoids the resection of bile duct and enables the administration of postoperative adjuvant therapies against recurrence and metastasis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%